Blockchain Technology – A Boon for The Banking Sector to Ensure Secure Transaction (International Journal of Food and Nutritional Sciences, 2022)
The technology driving blockchain transactions has recently emerged as a game-changingbreakthrough that has the ability to completely alter the way financial operations are carriedout.